2013
DOI: 10.4161/adip.26684
|View full text |Cite
|
Sign up to set email alerts
|

Is the lack of adiponectin associated with increased ER/SR stress and inflammation in the heart?

Abstract: Objective: To study whether there is an association between adiponectin and endoplasmic reticulum/sarcoplasmic reticulum (eRsR) stress.Research design: eleven-month-old male wild-type (WT) and adiponectin knockout (ADKO) mice were placed on chow or high fat diet for 12 weeks. The changes in eR stress and inflammatory genes were determined in the epididymal adipose, as well as heart tissue of adult WT and ADKO mice. To understand the role of eR/sR stress in the regulation of adiponectin, we studied the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Furthermore, adiponectin gene therapy has been demonstrated to restore SERCA gene expression in skeletal muscle of rats fed a high-fat diet, with further benefits resulting from combination therapy involving adiponectin and 9-weeks of aerobic swim training (Safwat et al 2013). This result has also been confirmed in H9C2 cells, where cardiomyocytes cultured in an adiponectin-enriched medium for 1 h demonstrated a 30% increase in SERCA2a mRNA compared with cells cultured in an adiponectin-depleted medium (Boddu et al 2014). Although the precise mechanism by which adiponectin enhances SERCA2a activity has yet to be fully elucidated, it may occur through an increased phosphorylation of the regulatory molecule PLN.…”
Section: Hormonal Regulation Of Serca2amentioning
confidence: 51%
“…Furthermore, adiponectin gene therapy has been demonstrated to restore SERCA gene expression in skeletal muscle of rats fed a high-fat diet, with further benefits resulting from combination therapy involving adiponectin and 9-weeks of aerobic swim training (Safwat et al 2013). This result has also been confirmed in H9C2 cells, where cardiomyocytes cultured in an adiponectin-enriched medium for 1 h demonstrated a 30% increase in SERCA2a mRNA compared with cells cultured in an adiponectin-depleted medium (Boddu et al 2014). Although the precise mechanism by which adiponectin enhances SERCA2a activity has yet to be fully elucidated, it may occur through an increased phosphorylation of the regulatory molecule PLN.…”
Section: Hormonal Regulation Of Serca2amentioning
confidence: 51%
“…Adiponectin is expressed and secreted by human and murine cardiomyocytes, where it enhances glucose and fatty acid uptake, suggesting a role of adiponectin in regulating cardiac metabolism and function [ 222 ]. In hearts from adiponectin-knockout mice, there is an increased expression of endoplasmic reticulum stress and inflammatory genes such as TNFα and MCP-1, an effect that is reverted by adiponectin treatment of H9C2 cardiomyocytes with induced endoplasmic reticulum stress and in HUVECs in sepsis [ 223 , 224 ]. In the same line, several studies have shown that adiponectin also protects the heart from I/R injury through the inhibition of endoplasmic reticulum stress [ 225 , 226 , 227 ] and that TNFα antagonism improves myocardial I/R injury by upregulating adiponectin expression in mice [ 228 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…90 Adiponectin shows efficient cardioprotective effect by facilitating recovery of SERCA2a activity through lowering inflammation and ameliorating ER stress in animal models with heart failure. 90,91 The regulation mechanism of adiponectinon is further investigated, during which increased phosphorylation level of PLN is always viewed, 90 although the precise role remains mysterious. Furthermore, adiponectin can also affect on the signalling of adenosine monophosphate-activated protein kinase (AMPK), 92 which plays a pivotal role in energy homeostasis and induces the alteration of SERCA1a protein and SERCA2a mRNA.…”
Section: Regulation Of Serca2a Expression and Activity In The Heartmentioning
confidence: 99%